Bordieuan Field Theory as an Instrument for Military Operational Analysis - Gunneriusson, Håkan (New Security Challenges,, 2017)
This book is open access under a CC BY 4.0 license. This book uses Pierre Bourdieu's field theory as a lens through which to examine military operations. Novel in its approach, this innovative text provides a better, more nuanced understanding of the modern 'battlespace', particularly in instances of prolonged low-intensity conflict. Formed in two parts, this book primarily explores the scope of Bourdien theory before secondly providing a detailed case study of the Yugoslavian succession war of 1990-1992. Gunneriusson suggests that although theories do not necessarily provide answers, they do help us ask better questions. This volume suggests news lines of interdisciplinary investigation that will be of interest to members of armed forces, practitioners from NGOs, and policymakers.